Pragmatic Study of Deixis in "Never Let Me Go": Exploring Meaning and Narrative Interaction (Journal of the College of Basic Education, 2025)
Human communication depends on language, and in order to comprehend meaning in any language, we must comprehend the context of communication, which includes time, place, and culture. Since every word relates to something different depending on the speaker's intended meaning, language and context are inextricably linked. Thus, there needs to be a connection between language and context. Deixis, however, can be used to identify this link. Deixis is a term that illustrates how contextual information is necessary to comprehend the meaning of a particular phrase or word. As a result, the deixis reference typically varies depending on the communication situation. Kazuo Ishiguro's novel "Never Let Me Go" featured this study on deictic expressions. The researcher analyzes deixis expressions using a descriptive-qualitative approach. This study uses Levinson's deixis categorization to perform a statistical analysis of the data. All of the novel's sentences serve as the data for analysis. Reading the text, recognizing deixis, categorizing different types of deixis, and providing examples of each are the methods modified to study the script. Next, elucidating the roles of each type of deixis. Since the novel is part of tragedy art, the plot takes place in unusual life, and the lines are in spoken language, thus the researcher chooses to investigate it and finds suitable material for deixis analysis. Thus, the author conducts the study labeled "pragmatics analysis of deictic expressions in this work. According to the study's findings, this novel contains 8100 deictic expressions in total. Personal Deixis (49.38%) and Discourse Deixis (17.65%) are the two most prevalent types of deixis in the novel. Next are Temporal Deixis (13.21%), Spatial Deixis (11.48%), and Social Deixis (8.27%). The study's goals are to: (1) identify the many kinds of deixis in Ishiguro's novel "Never Let Me Go". (2) describing how each sort of deixis is used in the novel; (3) indicating how frequently deictic terms are used in the novel .The following succinctly describes the significance of this study:One of the best novels in tragic art is , which looks to have a lot of deictic terms in its vocabulary. This has not yet been mentioned in scholarly research.Academic significance: this study explores the key elements of tragedy novels and may help other researchers conduct more studies on deictic expressions in tragic novels.English language learners and instructors will recognize the importance and usage of deixis expressions, which demonstrate that comprehending the meaning of a particular phrase or word necessitates a thorough comprehension of contextual information